Considering the Impact of a 12-Week Intervention Program on Behavioral Intentions and Key Health-Related Constructs in Adolescent Basketball Players - Jin Zhao; Wannaporn Sumranpat Brady (Physical Education Theory and Methodology)
Objectives. This study aimed to evaluate the impact of a 12-week basketball intervention program on adolescents’ behavioral intentions and key health-related constructs, including self-efficacy, social support, situational factors, and outcome expectations, based on the social cognitive theory (SCT), focusing on each gender and comparing both genders.